Study of olive pomace antioxidant dietary fibre powder throughout gastrointestinal tract as multisource of phenolics, fatty acids and dietary fibre - Ribeiro, Tânia (2021)
Pulp-enriched powder (POPP) was obtained from olive pomace solid fraction, a derived from the new value chain established for olive by-products. As a multifunctional powder, POPP retains several bioactive compounds (fatty acids, dietary fibre and phenolics) under potential synergic interaction, even more, reactive throughout the digestion. So, in this study, the potential multifunctionality of POPP was evaluated after the gastrointestinal tract. A significant loss of phenolics occurred during oral digestion (62.48 %). However, the potential role of dietary fibre as phenolics’ carrier and its possible liberation in the stomach allowed recovering a significant amount of phenolics (77.11 %) and a bioaccessibility index of at least 50 % (mainly for tyrosol and its glucoside). POPP also provides high content of dietary fibre mainly insoluble fibre (69.68 g/100 g dry weight) linked to a substantial amount of bound phenolics (7.63 mg of gallic acid equivalents/g fibre dry weight), with a positive effect on the fatty acids bioaccessibility [decreased the saturated (5-6 %) and facilitated the unsaturated fatty acids bioaccessibility (4-11%)]. PCA analysis became evident the negative effect of simulated gastrointestinal digestion upon POPP as mainly linked to phenolics’ loss. Despite all negative effects of the simulated digestion on POPP bioactive composition, phenolics and unsaturated fatty acids showed to be bioaccessible in significant amount, and the amount of bound phenolics associated to fibre retained in the colon have the potential to exert gut health benefits.